Wastewater Treatment and Water Reuse Technologies for Sustainable Water Resources: Jordan as a Case Study - Qteishat, Omar; Radideh, Jamal; Alzboon, Kamel; Abu-Hammateh, Ziad; Al-Azab, Tariq; Abu-Hammad, Numan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Due to the escalating water demands, in addition to sever water shortage, Jordan has done the most, making reuse a priority in their national water resources strategy. The waste stabilization ponds (WSP) represent the most economical method for wastewater treatment. For these reasons, many treatment plants were built in Jordan Since 1984 where more than 78% of all wastewater discharges had been treated in WSP. Recently, most of these plants were changed to mechanical technologies.
Keywords: wastewater; treatment; water reuse; wastewater technologies; reuse standards